Timely initiation of complementary feeding practices and associated factors among children aged 6-23 months in Dessie Zuria District, Northeast Ethiopia: a community-based cross-sectional study - Anteneh Demelash Abate; Seid Legesse Hassen; Minwuyelet Marru Temesgen (Frontiers Media S.A., 2023)
IntroductionEthiopia has one of the highest infant and child mortality rates in the world. Starting from the age of 6 months, breast milk alone is not sufficient to cover all nutritional requirements. Infants and young children are at an increased risk of undernutrition. Complementary feeding must, therefore, begin at the age of 6 months. Infant and young child nutrition is a critical factor in human health, nutrition, survival, growth, and development. Therefore, the aim of this study is to evaluate the timely initiation of complementary feeding practices and associated factors in children aged 6-23 months in the Dessie Zuria District of North Ethiopia.MethodsA community-based cross-sectional study design was used for the period between 16 March and 30 March 2019. The study included 770 mother-child pairs aged 6-23 months. A multistage sampling method was used to choose the study participants. Using a simple random sampling technique, nine kebeles in the district were selected from a total of 31, and from 103 Gotts or villages, 31 were selected with 770 HHs out of 2,329 HHs with children aged 6-23 months. Data were collected using a pretested semistructured interviewer-administered questionnaire, which was then entered into Epi Data version 3.1 statistical software before being transferred to SPSS version 21 for further analysis. To summarize the data, descriptive statistics were used, which included a simple frequency table and figures. To evaluate factors, bivariate and multivariable logistic regression were used. A p-value of less than 0.05 was used to determine statistical significance.ResultsThe percentage of children who started complementary feeding practices on time was 70.9. Maternal occupation [AOR = 5.51, 95% CI (1.61-18.81)], radio availability [AOR = 2.03, 95% CI (1.32-3.12)], antenatal care follow-up [AOR = 6.19, 95% CI (4.08-9.40)], place of delivery [AOR = 5.06%, CI (3.34-7.68)], and postnatal care follow-up [AOR = 4.32, 95% CI (2.77-6.72)] were found to be the factors for the timely initiation of complementary feeding.ConclusionWhen compared with WHO cutoff points, timely initiation of complementary feeding practice was relatively low in the study area. Maternal occupation, radio availability, ANC follow-up, place of delivery, and postnatal care visit were all significantly associated with the timely initiation of complementary feeding.